Nurturing pillars of society : understanding and working with the young generation in Hong Kong - Lee, Francis Wing-lin (Hong Kong University Press, 2011)
This book categorizes the young generation into three categories: Youth in General (Young People), Youth-at-Risk and Young Offenders. Besides describing how they should be perceived and introducing some concerned Indigenous studies, how they should be worked with/disposed locally are suggested. Some current juvenile justice issues are discussed near the end.